NATIONAL RESILIENCE STRENGTHEN THROUGH THE RESERVE COMPONENT TO RESIST NON-MILITARY THREATS - Zacharia RD, Agape; Ahmadani, Faisal; Danianto, Patria (International Journal of Research -GRANTHAALAYAH, 2021)
National Resilience is a nation dynamic condition, and a nation struggle to achieve national goal will be disturbed. National identity, national integration and national life sustainability have stronger than threat, challenge, disturbance and obstacle. This research uses qualitative research method to analyze potential threat, challenge, disturbing and obstacle for Indonesia, which come both from internal and external sources and national resources to face them. , potential threat will be dominated by nonmilitary threat. The Indonesia Armed Forces ( Nasional Indonesia), as the main component in Indonesia should face the potential threat. But TNI has its limitations, supporting power is necessary, and one of the potential powers is national resources which or converted to reserve component. The role of reserve component in future will contribute to Indonesia national resilience strengthen efforts.